2017
DOI: 10.3390/molecules22030426
|View full text |Cite
|
Sign up to set email alerts
|

Chroman-4-One Derivatives Targeting Pteridine Reductase 1 and Showing Anti-Parasitic Activity

Abstract: Flavonoids have previously been identified as antiparasitic agents and pteridine reductase 1 (PTR1) inhibitors. Herein, we focus our attention on the chroman-4-one scaffold. Three chroman-4-one analogues (1–3) of previously published chromen-4-one derivatives were synthesized and biologically evaluated against parasitic enzymes (Trypanosoma brucei PTR1–TbPTR1 and Leishmania major–LmPTR1) and parasites (Trypanosoma brucei and Leishmania infantum). A crystal structure of TbPTR1 in complex with compound 1 and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 44 publications
3
63
0
1
Order By: Relevance
“…Inhibitors of Pteridine Reductase 1 (PTR1) proved to be lethal to the parasites in Leishmania spp. and Trypanosoma brucei, but not in human cells [4].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Inhibitors of Pteridine Reductase 1 (PTR1) proved to be lethal to the parasites in Leishmania spp. and Trypanosoma brucei, but not in human cells [4].…”
Section: Introductionmentioning
confidence: 83%
“…Previous studies have reported as the PTR1 as an important target chemotherapeutic [3,4]. Inhibitors of Pteridine Reductase 1 (PTR1) proved to be lethal to the parasites in Leishmania spp.…”
Section: Introductionmentioning
confidence: 99%
“…Crystallization was performed by the hanging-drop vapordiffusion technique at room temperature (Benvenuti & Mangani, 2007). Well ordered monoclinic crystals of histidinetagged TbPTR1 grew within a few days (to final dimensions of $600 Â 200 Â 50 mm) using a precipitant solution composed of 2-2.5 M sodium acetate, 0.1 M sodium citrate pH 5, as described elsewhere (Di Pisa et al, 2017). A dimethylsulfoxide (DMSO) solution of the compound was added to the cryoprotectant [composed of the precipitant enriched to 30%(v/v) glycerol] to a final concentration of 4 mM [the DMSO concentration was kept lower than 10%(v/v)].…”
Section: Protein Crystallizationmentioning
confidence: 99%
“…The TbPTR1 inhibitors developed to date were conceived as substrate-competitive inhibitors and are based on a wide variety of scaffolds, including 2,4-diaminopteridine (Dawson et al, 2006;Tulloch et al, 2010), quinazoline (Dawson et al, 2010), 2,4-diaminopyrrolopyrimidine (Tulloch et al, 2010), chromone (Borsari et al, 2016;Di Pisa et al, 2017), 2-aminothiadiazole (Linciano et al, 2017), 2-aminobenzimidazole (Mpamhanga et al, 2009), triazine (Tulloch et al, 2010), 1,6-dihydrotriazine (Landi et al, 2019) and 2-aminobenzothiazole (Linciano et al, 2019). More than 60 crystal structures of TbPTR1-inhibitor complexes have now been deposited in the Protein Data Bank (PDB), clarifying the key binding interactions that occur inside the catalytic cavity (Pozzi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some chroman and chromene derivatives have exhibited DNA gyrase inhibition, and within the chromanones, a hydrogen bond donor/acceptor functionality at the 4-position together with a lipophilic 2-alkyl moiety is believed to be important for antibacterial activity. Much interest has focused on the use of chromenes as antiparasitic agents, with chromen/chroman-4-ones suggested to exert their effects through pteridine reductase 1 (PTR1) inhibition within both Trypanosoma brucei and Leishmania species (Di Pisa et al, 2017).…”
Section: Phytochemistrymentioning
confidence: 99%